Tear proteome profile in eyes with keratoconus after intracorneal ring segment implantation or corneal crosslinking - Goñi, Nahia; Martínez-Soroa, Itziar; Ibarrondo, Oliver; Azkargorta, Mikel; Elortza, Felix; Galarreta, David J.; Acera, Arantxa (Frontiers in Medicine, 2022)
Purpose: Keratoconus (KC) is a corneal ectasia characterized by structural changes, resulting in progressive thinning and biomechanical weakening that can lead to worsening visual acuity due to irregular astigmatism. Corneal collagen Crosslinking (CXL) and Intracorneal Ring Segment (ICRS) are widely used treatments in KC disease, but the alterations they cause in biomechanical mediators are still poorly understood. The aim of this study was to analyze the tear proteome profile before and after treatments to identify biomarkers altered by surgery. Methods: An observational, prospective, case-control pilot study was conducted, analyzing tear samples from KC patients by nano-liquid chromatography-mass spectrometry (nLC-MS/MS). Data are available via ProteomeXchange with identifier PXD035655. Patients with KC who underwent ICRS surgery (n=4), CXL (n=4), and healthy subjects (Ctrl, n=4) were included in this study. Clinical parameters were measured and tear samples were collected before and 18 months after surgery. Proteins with ≥2 expression change and p-value <0.05 between groups and times were selected to study their role in postoperative corneal changes. Results: These analyses led to the identification of 447 tear proteins, some of which were dysregulated in KC patients. In comparisons between the two surgical groups and CTs, the biological processes that were altered in KC patients at baseline were those that were dysregulated as a consequence of the disease and not of the surgical intervention. Among the biological processes seen to be altered were: immune responses, cytoskeleton components, protein synthesis, and metabolic reactions. When comparing the two treatment groups (ICRS and CXL), the process related to cytoskeleton components was the most altered, probably due to corneal thinning which was more pronounced in patients undergoing CXL. Conclusion: The changes observed in tears after 18 months postoperatively could be due to the treatments performed and the pathology. Among the deregulated proteins detected, AKAP-13 deserves special attention for its involvement in corneal thinning, and for its strong overexpression in the tears of patients with more active KC and faster disease progression. However, it should be kept in mind that this is a pilot study conducted on a small number of patients.